Prevalence estimates of Helicobacter species infection in pancreatic and biliary tract cancers. Issue 1 (10th January 2022) - Osaki, Takako; Lin, Yingsong; Sasahira, Naoki; Ueno, Makoto; Yonezawa, Hideo; Hojo, Fuhito; Okuda, Masumi; Matsuyama, Masato; Sasaki, Takashi; Kobayashi, Satoshi; Tezuka, Shun; Tanaka, Kei; et al.
Abstract: Background: Helicobacter pylori infection is a well‐established risk factor for gastric cancer and has been linked to other gastrointestinal diseases, including pancreatic and biliary tract cancers; however, the relevance of enterohepatic non‐ H. pylori helicobacters to the pathophysiology of these diseases remains unclear. Materials and Methods: We estimated the prevalence of two enterohepatic non‐ H. pylori helicobacters ( Helicobacter hepaticus and Helicobacter bilis) in the framework of a hospital‐based case‐control study involving 121 patients with biliary tract cancer, pancreatic cancer, or other gastrointestinal diseases. Bile and blood samples were collected from the patients undergoing endoscopic retrograde cholangiopancreatography. The presence of H. bilis, H. hepaticus, and other Helicobacter spp. was examined using bacterial culture, PCR‐based detection, and serological tests. Results: Culture of Helicobacter spp. from biliary brush samples was unsuccessful. Approximately 13.0% (15/115) of the bile samples collected from patients with a variety of gastrointestinal cancers, including pancreatic and biliary tract cancers, tested positive for one of the enterohepatic non‐ H. pylori helicobacter species as determined by PCR. Specifically, H. bilis and H. hepaticus DNA were detected in 11 and 4 bile samples, respectively. Approximately 20%–40% of the patients tested positive for serum non‐ H. pylori helicobacter IgG antibodies. The seroprevalence of H. bilis and H. hepaticus in the patients without evidence of H. pylori infection appeared to be higher in the pancreatic cancer group than in the control group. Conclusion: Our findings suggest a role for Helicobacter spp., especially H. bilis and H. hepaticus, in the etiology of pancreatic and biliary tract cancers.